1993
DOI: 10.1002/ddr.430290308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the PAF antagonists bepafant and L‐659, 989 in endotoxic and septic shock

Abstract: Many of the pathophysiological effects of endotoxin (ETX) can be mimicked by the administration of platelet activating factor (PAF), and the latter has been implicated as a possible mediator of the derangements seen in endotoxic shock. In this investigation, two new potent PAF antagonists, bepafant (WEB-2170) and L-659,989, were studied for their effects in experimental endotoxic and septic shock in rats. Pretreatment with the PAF antagonists, 15 min prior to the iv administration of Escherichia coli endotoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Earlier results from animal studies of endotoxin-induced sepsis showed that lexipafant, the potent PAF receptor antagonist used in this study, reduced TNF production by 40% compared to that in placebo-treated animals (12). B. pseudomallei is the most common cause of community-acquired septicemia in northeast Thailand, especially in the rainy season (4).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Earlier results from animal studies of endotoxin-induced sepsis showed that lexipafant, the potent PAF receptor antagonist used in this study, reduced TNF production by 40% compared to that in placebo-treated animals (12). B. pseudomallei is the most common cause of community-acquired septicemia in northeast Thailand, especially in the rainy season (4).…”
Section: Discussionmentioning
confidence: 68%
“…When administered systemically to animals, it produces many of the features of septic shock. In experimental septic shock, blocking either the proinflammatory cytokines TNF and interleukin 1 (IL-1) or lipid mediators such as PAF decreases the severity of the disease (12,13). In one study, the PAF antagonist BN 52021 was shown to be a safe and promising treatment of patients with severe gram-negative sepsis (6).…”
mentioning
confidence: 99%
“…Upon overwhelming stimulation, the immune system becomes excessively activated, resulting in a dysfunctional immune response, which contributes to multi-organ dysfunction syndrome, and ultimately, lethality ( 5 , 6 ). In this context, previous studies in cecal ligation and puncture-induced rodent sepsis reported some beneficial effects by inhibiting PAF activity ( 7 ). However, despite initial encouraging results in a phase II study ( 8 , 9 ), PAF degradation ( 10 ) or administration of PAF receptor antagonists ( 11 ) failed to reduce lethality in patients with severe sepsis.…”
Section: Introductionmentioning
confidence: 90%
“…The involvement of P AF in endotoxic shock was evaluated by the following observations: (1) Administration (infusion) of PAF mimics effects of endotoxin or rather the state of shock (McMANUS et al 1980), even if its action is more venoconstrictive than arterioconstrictive (BAR-NATAN et al 1995); (2) endotoxin induces rise of PAF in blood (CHANG et al 1987;DOBROWSKY et al 1991), or rather PAF is generated during the state of shock (PINCKARD et al 1979) produced by lung and liver (ANDERSON et al 1991;RABINOVICI et al 1991), which is paralleled by a decrease in acethydrolase (NARAHARA and JOHNSTON 1993); endotoxin may also activate PAF receptors (NAKAMURA et al 1992;WAGA et al 1993); (3) PAF rises in blood before TNF rises (DOEBBER et al 1985), with PAF antagonists impeding TNF rise and action (FLOCH et al 1989;FERGUSON-CHANOWITZ et al 1990;RUGGIERO et al 1994); (4) synergistic effects of P AF and LPS at the cellular level have been reported (PIRES et al 1994;FOUDA et al 1995), and (5) specific PAF antagonists improve survival and provide significant protection against the state of shock (DOEBBER et al 1985;TERASHITA et al 1985;INNAREA et al 1985;ETIENNE et al 1986;ADNOT et al 1986;HANDLEY et al 1986;CASALS-STENZEL 1987c;YUE et al 1990a;TANG et al 1993) or against lung injury by endotoxin (CHANG et al 1987(CHANG et al , 1990OLSON et al 1990a,b).…”
Section: P Af In Endotoxin-induced Shockmentioning
confidence: 99%